Who Escaped Poverty and Who Was Left Behind? A Non-Parametric Approach to Explore Welfare Dynamics Using Cross-Sections - Lucchetti, Leonardo (World Bank E-Library Archive, 2017)
This paper proposes a non-parametric adaptation of a recently developed parametric technique to produce point estimates of intra-generational economic mobility in the absence of panel data sets that follow individuals over time. The method predicts past individual income or consumption using time-invariant observable characteristics, which allows the estimation of mobility into and out of poverty, as well as household-level income or consumption growth, from cross-sectional data. The paper validates this method by sampling repeated cross-sections out of actual panel data sets from three countries in the Latin America region and comparing the technique with mobility from panels. Overall, the method performs well in the three settings; with few exceptions, all estimates fall within the 95 percent confidence intervals of the panel mobility. The quality of the estimates does not depend in general on the sophistication level of the underlying welfare model's specifications. The results are encouraging even for those specifications that include few time-invariant variables as regressors